Equity valuation P/F Bakkafrost - Mathiesen, Christian Martin (2014)
Bakkafrost is one of the most efficient salmon farmers in the industry, and the farming conditions on the Faroe Island, where the company resides, are above average. These factors will surely serve as a great advantage as the industry enters a period of a strong Atlantic salmon price. The salmon price is estimated by simulations on historical price data, which gives relatively conservative results. This matters little considering that the majority of the value stems from the terminal value, which is based on the average historical price. Bakkafrost has just initiated a 5 year investment program to centralize their operations and reduce costs. This valuation uses a forecast period of 5 years thus incorporating the cash flows related to the program. The resulting cost savings are accounted for in the terminal value of the valuation. This report is based on thorough investigation of public information, and considerable care was taken to make appropriate assumptions about the continued operations of Bakkafrost. The valuation was done using an enterprise DCF, which considers estimates for both cash flows and exposure to market risk.